KAROMAH KH. LATHIFI BAIDHOWI DI DESA SUKOSARI KECAMATAN GONDANGLEGI KABUPATEN MALANG - Syaifudin Zuhri; Moh. Ahsan Shohifur Rizal (Jurnal Tradisi Lisan Nusantara, 2022)
Abstract: The aims of this research are (1) Social, Cultural and Religious Aspects in the Folklore of Karomah KH. Lathifi Baidhowi (2) describes the socio-cultural aspects contained in folklore, (3) explains the functions and public responses to folklore, (4) describes the implementation of folklore as teaching material for Indonesian literature at IAI AL-Qolam. This study uses a qualitative descriptive method, using a fixed case study design strategy. The data in this study are in the form of sentences and paragraphs. There are two sources of data in this study, namely primary data sources originating from informants or sources at the folklore place of Karomah KH. Lathifi Baidhowi is here. Sources of secondary data in the study came from stories in the Biography book and data from interviews with the Community/Santri. Data collection techniques in this study through in-depth interviews, observation, and documentation. The data analysis technique used in this study is a qualitative data analysis technique using an interactive analysis model. The results of this study are four (1) the origin and structural analysis of the folklore of Karomah KH. Lathifi Baidhowi the theme of folklore is about people's belief in stories. The plot used is a forward plot, the character in the story of Karomah KH Lathifi as Msrsyid Toriqoh who makes accusations to several areas around East Java. The setting of the story is divided into two,namely the setting of the place and the setting of time. (2) The social aspects of thisfolklore include social aspectsrelated to religiousissues, cultural aspects in this study include people's beliefs. (3) Community responses and the function of folklore, namely the benefits of several Karomah and ritual worship activities according to Islamic teachings. (4) Implementation of the folklore of Karamah KH. Lathifi Baidhowi as a literature teaching material at IAI Al-Qolam is appropriate and relevant and can be used as literature learning material.